RISIKO USAHATANI UBI ALABIO (DIOSCOREA ALATA L.) DI DESA SUNGAI AMBANGAH KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Mayang Putri; Dewi Kurniati; Maswadi Maswadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Alabio sweet potato (Dioscorea alata L.) is a palawija crop that has potential for alternative food. Risk is the possibility of loss arising from conditions beyond the farmer's control. This study aims to identify the risk level of Alabio sweet potato (Dioscorea alata L.) farming and formulate efforts to reduce the risk of Alabio sweet potato (Dioscorea alata L.) farming. Respondents were 25 farmers of Alabio sweet potato (Dioscorea alata L.) in Sungai Ambangah Village, Sungai Raya District, Kubu Raya Regency. The analytical tool used is the Coefficient of Variation Analysis to measure the level of risk faced by farmers and the Fishbone Diagram to identify problems to find solutions. The results of this study are that the level of production risk and the level of income risk have a coefficient of variation (CV) > 0.5, meaning that the risks faced by farmers are large. The sources of risks that occur are high rainfall, plant pests and diseases, fluctuating input prices, inactive agricultural extension assistance, limited farming capital and no farmer groups.